2014
DOI: 10.1186/preaccept-1619001546133883
|View full text |Cite
|
Sign up to set email alerts
|

Replication competent virus as an important source of bias in HIV latency models utilizing single round viral constructs

Abstract: The central memory T cell (TCM) model forms a unique HIV-1 latency model based on primary cells that closely resemble in vivo TCM. The virus employed in this model is based on an engineered vector incapable of replication after initial infection. We show that despite this strategy, replication competent viral particles are released into the culture medium due to recombination between overlapping sequences of the env deleted HIV genome that is co-transfected with intact env. This finding emphasizes the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Compared to αCD3/αCD28-stimulated cells at 6 days postinfection, untreated resting CD4 + T cells showed significantly lower levels of HIV infection but, nonetheless, permitted both productive and latent infection (Fig 1C). Importantly, productive and latent infection of resting CD4 + T cells over the 6-day time-course was not the result of replication-competent virus being present in our HIV Duo-Fluo I viral stocks (S2 Fig) [48]. …”
Section: Resultsmentioning
confidence: 99%
“…Compared to αCD3/αCD28-stimulated cells at 6 days postinfection, untreated resting CD4 + T cells showed significantly lower levels of HIV infection but, nonetheless, permitted both productive and latent infection (Fig 1C). Importantly, productive and latent infection of resting CD4 + T cells over the 6-day time-course was not the result of replication-competent virus being present in our HIV Duo-Fluo I viral stocks (S2 Fig) [48]. …”
Section: Resultsmentioning
confidence: 99%
“…A recent study indicated that HIV-1 constructs rendered incapable of replicating by mutations or deletions of the env gene can revert to wild type through recombination with envelope expression plasmids following co-transfection of producer cells [ 51 ]. To test if replication competent viruses might be contributing to our results, we treated infected resting CD4 T cells with the protease inhibitor indinavir on the day of infection and on day 5 post infection with the non-nucleoside reverse transcriptase inhibitor efavirenz in order to block the spread of any reverted viruses.…”
Section: Response Of Latent Unintegrated Vs Integrated Hiv-1 To a Sementioning
confidence: 99%
“…When samples from a single donor were profiled over time, a large number of genes were identified as dysregulated during the latent phase (N = 227) and were associated with chemokine receptors, cytokine signaling, and general immune responses. We previously used RNA-Seq to profile latently infected and uninfected samples from 4 donors [17] from the first iteration of a cultured primary central memory CD4 T cell (T CM ) model [18,19]. This study demonstrated that the defective vectors used to seed the latent reservoir were recombining to reconstitute actively replicating HIV-1.…”
Section: Introductionmentioning
confidence: 99%